Cardiovascular and perceived effort in different head‐out water exercises: effect of limbs’ action and resistance equipment - Costa, M.J. (2019)
The aim of this study was to compare the cardiovascular and perceived effort of head‐out water exercises selecting different limb strategies and using resistance equipment. Ten young women were randomly assigned to perform at 132 bpm during five minutes different head‐out aquatic exercises: (i) horizontal arms abduction (Ab); (ii) horizontal arms abduction with dumbbells (AbD); (iii) frontal kick (Fk); (iv) frontal kick with leggings (FkLeg), and; (v) aquatic skiing (Ski). Cardiovascular effort was measured by monitoring the heart rate, blood pressure and double product. Perceived effort was assessed by the Borg’s scale. Within‐routines comparison was computed using repeated measures ANOVA followed‐up by the Bonferroni post‐hoc test. Considering the percentage of the maximal heart rate, participants reached 72.88 ± 12.90% in the FkLeg, 65.99 ± 10.91% in the Fk, 62.62 ± 7.20% in Ski, 57.27 ± 11.58% in AbD and 57.12 ± 12.09% in Ab. Comparing exercises, higher heart rates were observed in the FkLeg (140.40 bpm) than Ab (110.30 bpm) or AbD (110.00 bpm). Significant differences were found in the systolic blood pressure when compared to the Fk (120.60 mmHg) and Ab (104.50 mmHg). Double product was higher in the FkLeg (16990) showing a meaningful difference when compared to Ab (11608) or AbD (12001). The highest perceived effort was found in the FkLeg (15.80) with meaningful variations compared to Ab (11.70), the Fk (13.70) and Ski (10.40). Thus, different headout water exercises result in different intensities. The actions by lower limbs promote a higher cardiovascular response, whereas the upper limbs actions trigger a lower exertion. Moreover, exercising the four limbs concurrently seems to be less intense than using only two limbs with an aid.